Fraternal Relative Deprivation of a Tribal Population in Chittagong Hill Tracts, Bangladesh - Hossain, Md Kamal (Journal of Life and Earth Science, 2011)
The study investigated fraternal relative deprivation of a tribal population (Chakma) in connection with their education, residence and gender difference in the socio-political and economic conditions in the Chittagong Hill Tracts (CHT), Bangladesh. The study used a sample composed of 240 respondents. The Fraternal Relative Deprivation Scale (FRDS) was used for data collection. A 2????2????2 factorial design involving two levels of education (graduate vs. undergraduate), two levels of residence (urban vs. rural) and two levels of gender (male vs. female) was utilized. Analysis of Variance (ANOVA) was used for the analysis of data. Results show that undergraduate respondents expressed significantly higher intensity in perceived fraternal relative deprivation as compared to their graduate counterparts. Similarly, male respondents felt more relative deprivation as compared to the female respondents. Key words: Fraternal relative deprivatio;, tribal population; Chakma; egoistic relative deprivation; social identity DOI: 10.3329/jles.v3i0.7442 J. Life Earth Sci., Vols. 3-4: 29-32, 2009